Performance monitoring as fault detection approach on AC power output of monocrystalline grid-connected photovoltaics system - Muhammad, Nurmalessa; Zaid, Norsyafrina Abdul; Zainuddin, Hedzlin; Yunus, Puteri Nor Ashikin Megat (Institute of Advanced Engineering and Science, 2024)
As per the Malaysian sustainable energy development authority (SEDA), Malaysia has seen a significant growth in renewable energy thanks to the feed-in tariff (FiT) program. However, photovoltaic (PV) systems in tropical countries like Malaysia experience degradation due to technological factors and operating conditions. The effectiveness of PV systems is influenced by geographical location and weather conditions. This research study conducted a comparative analysis between the actual power output PAC_actual and the predicted power output PAC_expected, referred to as the acceptance ratio (AR). The study also assessed the yield and performance ratio (PR) of a PV system situated at the green energy research center (GERC) in Universiti Teknologi MARA, Malaysia. The actual monocrystalline grid-connected photovoltaic (GCPV) system versus predicted AC power and AR were monitored over a year, with MATLAB software used for simulating output power based on real data. According to the Malaysian Standard MS2692:2020, an AR value of 0.9 or higher is required for approval in testing and commissioning tests. The findings indicate that most AR graphs fall below this threshold, and the PR value for each month is below 0.75, suggesting a need for significant system overhaul.